לפתור את המשוואה הבאה ...? 2 ^ (4x) - 5 (2 ^ (2x - 1/2)) + 2 = 0

לפתור את המשוואה הבאה ...? 2 ^ (4x) - 5 (2 ^ (2x - 1/2)) + 2 = 0
Anonim

תשובה:

# x = ln ((25 + -sqrt (609)) / (2sqrt (2))) / (ln4) # #

הסבר:

# 2 ^ (4x) -5 (2 ^ (2x-1/2)) + 2 = 0 <=>

# 2 ^ (2x) ^ 2) 5 * 2 ^ (2x) צבע (אדום) (xx) 5 * 2 ^ (- 1/2) + 2 = 0 <=>

# 2 (2x) + 2 = 0 = = 2 (2x) + 2 = (25 / sqrt (2))

עכשיו את משוואה ריבועית צריך להיות קל לראות.

אתה צריך להחליף # 2 ^ (2x) # עם כל.

# <=> y ^ 2- (25 / (2)) y + 2 = 0 #

# y = (25 / sqrt (2) + - sqrt (625 / 2-2 * 2 * 2)) / 2 #

# y = (25 / sqrt (2) + - sqrt (609/2)) / 2 #

# 2 ^ (2x) = y = (25 / sqrt (2) + - sqrt (609/2)) / 2 #

שימוש בלוגריתמים:

# 2xln2 = ln ((25 + -sqrt (609)) / (2sqrt (2))) #

# x = ln ((25 + -sqrt (609)) / (2sqrt (2))) / (2ln2) # #

# x = ln ((25 + -sqrt (609)) / (2sqrt (2))) / (ln4) # #